HUMANISM OR ANTI-HUMANISM? DISCOURSE POSTMODERN - Фоменко, А. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The articledescribes thespecific features of Postmodern humanistic discourse on the basis of analysis of Western European Philosophy concepts.